Strategi Badan Usaha Milik Desa Dalam Mengembangkan Agrowisata Belimbing - Uswatun Khasanah; Isnaini Rodiyah (Univiversitas Dr. Djar Wattiheluw, 2024)
This study analyzes the BUMDes (Village-Owned Enterprises) strategy in developing Belimbing Agrotourism in Watesari Village. Utilizing a qualitative descriptive method, data is collected through observation, interviews, and supporting documentation, with key informants including the Village Head, Village Government, and BUMDes Bina Sejahtera Management. Findings, based on indicators proposed by Jack Kooten in Kasmira, reveal: 1) BUMDes Bina Sejahtera has established goals, vision, and a mission for Agrotourism Belimbing. 2) Agrotourism Belimbing introduced three programs, but they are not fully realized. 3) Human resources at BUMDes Bina Sejahtera do not meet requirements in quality and quantity, and financial resources are insufficient, planned for the following year. 4) Organizational structure is formed but not operating optimally; BUMDes has not collaborated with third parties, private sector or government.